E-crm application of micro, small and medium enterprises in sri lanka: mixed method - Sathana, V. (University of Jaffna, 2022)
Small Medium Enterprise (SME) sector plays prominent role to the development of Sri Lanka, and they have been facing huge problem and challenges in this competitive and crisis environment. Previous researchers have conducted research on e-CRM application for large firms and proved the e-CRM’s significant for large firms. Still e CRM application is debatable in developing countries. The purpose of this research is to find out the ubiquitous e-CRM application for the success of Sri Lankan MSMEs, especially the factors of e-CRM in SME sector. Researcher applied mixed method in this research and respondents are the owners or managers of SMEs. Four focus group discussion and ten interviews were conducted for the qualitative research and snowball sampling techniques was applied to select the respondents for the quantitative method. The coding and thematic analysis were conducted to find out the themes of e-CRM of SMEs. From the qualitative analysis, fifteen themes were identified and they were come under the three dimensions. For the quantitative research, questionnaire was developed with 36 questions. The exploratory factor analysis was conducted to find out the factors of e-CRM of SMEs. Four dimensions were identified from the exploratory factor analysis. Factor 1 is named as E-CRM in Marketing, factor 2 is denoted as E CRM implementation, factor 3 is called as Strategic integration and factor 4 is referred as Technology-based CRM. The application of four dimensions of e-CRM enable the SMEs to keep existing customers and attract the new customer.
Keywords: SME; E-CRM in Marketing; E-CRM implementation; Strategic integration; Technology-based CRM